Potential of Active Compounds in Broadleaf Mahogany (Swietenia macrophylla) Seeds Against Breast Cancer Cells Based on In Silico Study - Cahya, Hanifah Dwi; Nurlela, Nurlela; Tohir, Dudi; Batubara, Irmanida; Asoka, Shadila Fira; Yamauchi, Kosei (Tropical Biopharmaca Research Center, IPB University, 2024)
Breast cancer is a leading cause of cancer-related deaths in Indonesia. However, the drugs that are commonly used for treatment can cause side effects and become resistant over time. A study was conducted to test the cytotoxic activity of broadleaf mahogany (Swietenia macrophylla) seed extract on MCF-7 breast cancer cells in vitro. The study aimed to predict active compounds in the broadleaf mahogany seeds that have the potential to act as anti-breast cancer agents using in silico analysis. Molecular docking, visualization of the interaction between the receptor and the ligands, and physicochemical analysis were used to determine the most promising compounds. The receptors used were fibroblast growth factor receptor 1 (FGFR1), vascular endothelial growth factor receptor 2 (VEGFR2), insulin-like growth factor type 1 receptor (IGF-1R), estrogen receptor (ER-α), and progesterone receptor (PR). The results showed that 12 compounds have the potential to be active as anti-breast cancer agents. Three of these compounds, 3β,6-dihydroxydihydrocarapine, stigmasterol, and 7-hydroxy-2-(4-hydroxy-3-methoxyphenyl)-chroman-4-one, were predicted to have similar mechanisms of inhibition as a comparator drug based on binding site similarity values. These compounds are predicted to be taken orally and are promising for further research.